Orientation, attitude, and competency as predictors of manager's role of CSR‐implementing companies in Malaysia. Issue 5 (2014) - ,; ,; ,; ,
Abstract : Purpose – This exploratory study aims to investigate how the role of the CSR manager is influenced by his orientation to corporate social responsibility (CSR) responsibilities, his attitude and competency.Design/methodology/approach – The study involved 112 managers of CSR‐implementing companies in the Klang Valley, a highly industrialized region in Malaysia. They were chosen based on a systematic random sampling technique.Findings – The study found that the level of role, orientation and competency of CSR managers was high, whereas that for attitude was moderate. Further, regression analysis results showed that the managers' orientation to economic and ethical responsibilities as well as competency significantly influenced their role in CSR with an explanatory power of 20.1 per cent.Research limitations/implications – The study was cross‐sectional in nature. Nevertheless, it involved a sample of company managers from a selected location in the country. The predictor variables were limited to orientation to economic, legal, ethical and philanthropic responsibilities; attitude; and competency.Practical implications – The study highlights the importance of personal qualities of the manager and also the manager's role in promoting community development CSR. These findings should be capitalized on by managers and other practitioners in CSR.Originality/value – The study findings contribute to research on CSR that is viewed from the perspective of corporate image being projected by the role of CSR managers, as influenced by their CSR orientation, attitude and competency. Recommendations for CSR and human resource development practice and future research on the predictors of the role of CSR managers are proposed. Acknowledgements : The research was funded by Research University Grant Scheme (RUGS) 2010‐2012, Grant No: 06‐04‐10‐1019RU of Universiti Putra Malaysia, Serdang, Selangor, Malaysia.